Operationalizing household food security in development projects: an introduction - Hoddinott, John F. (International Food Policy Research Institute, 1999)
This introductory guide provides a brief introduction to the concept of food security. (An introduction to nutrition issues is found in Technical Guide #5.) It outlines the links between the types of projects often designed and their impact on food security and nutrition. By doing so, it provides a framework for thinking about what projects would be most appropriate in a given situation and indicates what types of information are needed in order to maximize impact on food security. It can also be the case that collaborators in developing countries are not always fully conversant with food security concepts. The material presented in this guide can also be used to sensitize such individuals. It also introduces the remaining ten guides, showing how using these can assist in easing information constraints often faced by development practitioners. By doing so, it should be possible to improve the targeting of interventions, to understand their likely effects, and to develop improved monitoring and evaluation methods.